Resilience as a Mediator for Relationships Between Religiosity and Social Support With Parents’ Psychological Well-Being - Zakiyah, Zein Noer; Karyani, Usmi (Jurnal Sains Psikologi, 2023)
During the Covid-19 pandemic, parents of students who carried out online learning were prone to experiencing low psychological well-being. Resilience is considered essential in mediating the relationship between religiosity and social support with psychological well-being. However, this role has yet to be tested empirically. This study examines the role of resilience as a mediator of the relationship between religiosity and social support with the psychological well-being of parents of students who carry out online learning during the Covid-19 pandemic. The research respondents totalled 281 parents living in the ex-Karesidenan Surakarta using the accidental sampling technique. Data analysis in this study used a simple mediation analysis with PROCESS macro analysis assisted by the SPSS v22.0 data analysis program. The study’s results prove that resilience mediates religiosity, social support, and psychological well-being. The mediation role of resilience is partial. The results of this study can be the basis for creating programs to improve the psychological well-being of parents through increased resilience, religiosity and social support.